Brock Biology of Microorganisms - Michael T Madigan (Pearson, 2019)
Brock Biology of Microorganisms is the leading majors microbiology text on the market. It sets the standard for impeccable scholarship, accuracy, and strong coverage of ecology, evolution, and metabolism. The 15th edition seamlessly integrates the most current science, paying particular attention to molecular biology and the genomic revolution. It introduces a flexible, more streamlined organization with a consistent level of detail and comprehensive art program. Brock Biology of Microorganisms helps students quickly master concepts, both in and outside the classroom, through personalized learning, engaging activities to improve problem solving skills, and superior art and animations with Mastering Microbiology.